Hypergammaglobulinemia is a marker of extraintestinal manifestations in pediatric inflammatory bowel disease - Manar Matar; Firas Rinawi; Raanan Shamir; Amit Assa (Turkish Journal of Gastroenterology, 2019)
Background/Aims: The significance of hypergammaglobulinemia as a phenotypic feature of inflammatory bowel disease is unknown. Thus, we aimed to analyze the magnitude and significance of hypergammaglobulinemia in newly diagnosed pediatric inflammatory bowel disease patients. Materials and Methods: The medical records of 296 pediatric onset inflammatory bowel disease patients who were evaluated from 2002 to 2015 were retrospectively reviewed. Patients with recorded immunoglobulin G (IgG) levels were categorized as either normal or high IgG levels at diagnosis. Baseline characteristics included age at onset, sex, severity indices, laboratory data, extraintestinal manifestations, endoscopic findings, and anthropometric measurements. Results: Of 184 subjects [mean age, 13.2±2.8 years; 105 (60%) males] with recorded IgG levels, 129 (70%) had Crohn disease, 46 (25%) had ulcerative colitis, and 9 (5%) had unclassified inflammatory bowel disease. Overall, 46 patients (25%) had hypergammaglobulinemia, including 30 (23%) with Crohn disease, 14 (30%) with ulcerative colitis, and 2 (22%) with unclassified disease. Hypergammaglobulinemia was associated with the female sex (55% vs. 35%; p=0.03) and extraintestinal manifestations (70% vs. 10%; p<0.0001), including arthritis, skin disorders, and primary sclerosing cholangitis but not with arthralgia. It was also associated with corticosteroid induction (68% vs. 45%; p=0.02) and maintenance with an immunomodulator (61% vs. 21%; p=0.0001) after diagnosis. In ulcerative colitis patients, hypergammaglobulinemia was associated with a high pancolitis prevalence (p=0.002). Conclusion: Hypergammaglobulinemia is a marker of extraintestinal manifestations in pediatric inflammatory bowel disease and may assist in distinguishing arthritis from arthralgia.